2009
DOI: 10.1111/j.1439-0396.2008.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary additives (potassium diformate/organic acids) as well as influences of grinding intensity (coarse/fine) of diets for weaned piglets experimentally infected with Salmonella Derby or Escherichia coli

Abstract: The aim of this study was to examine whether and to what extent the addition of potassium diformate (pdf) or free organic acids (fpa) to the diet and the grinding intensity might affect the course of infection and the passage of orally applied Salmonella and Escherichia coli in pigs. Experiments were carried out using 80 reared piglets allotted to four groups. Pigs were fed pelleted diets ad libitum (except during a 15 h feed-withholding-period before infection). The control diet contained finely ground cereal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 15 publications
(31 reference statements)
1
30
0
1
Order By: Relevance
“…Several studies have evaluated the effect on Salmonella control of on-farm treatment of feed or water with acids (Letellier et al, 2000;van der Wolf et al, 2001;Lo Fo Wong et al, 2004;Canibe et al, 2005;Farzan et al, 2006;Creus et al, 2007;Poljak et al, 2008;De Busser et al, 2009;Taube et al, 2009;Tanaka et al, 2010). The results varied greatly between studies, possibly because of the large differences in the acidification process and dosage used (O'Connor et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the effect on Salmonella control of on-farm treatment of feed or water with acids (Letellier et al, 2000;van der Wolf et al, 2001;Lo Fo Wong et al, 2004;Canibe et al, 2005;Farzan et al, 2006;Creus et al, 2007;Poljak et al, 2008;De Busser et al, 2009;Taube et al, 2009;Tanaka et al, 2010). The results varied greatly between studies, possibly because of the large differences in the acidification process and dosage used (O'Connor et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Weaned piglets given organic acids (like citric, fumaric, lactic and formic acids) showed improved growth performance and health (Edmonds et al, 1985;Giesting and Easter, 1985;Tsiloyiannis et al, 2001). In a study in-feed organic acids reduced Salmonella and E. coli counts in the stomach of experimentally infected piglets (Taube et al, 2009). Another study which performed a challenge test with organic acids is performed by Li et al (2008).…”
Section: Organic Acidsmentioning
confidence: 99%
“…Several studies have been performed to the effects of organic acids on pig performances (Edmonds et al, 1985;Giesting and Easter, 1985;Tsiloyiannis et al, 2001;Li et al, 2008;Apajalahti et al, 2009;Taube et al, 2009;Chu et al, 2013). Chu et al (2013) found that bamboo charcoal and bamboo vinegar (which contain organic acids) had a positive influence on growth performance, feed intake, immunoglobulin concentrations (IgG, IgA, and IgM), faecal Salmonella spp.…”
Section: Organic Acidsmentioning
confidence: 99%
“…Such feeding regimens include feed supplementation with organic acids which are available as commercial preparations and the modification of feed structure. Increased feed particle size and diet supplementation with organic acids resulted in reduced Salmonella numbers in the lower parts of the gastrointestinal tract, decreased fecal shedding of this pathogen in pigs, and subsequently the reduced prevalence of Salmonella on pig farms (40,45,54,55). However, limited information is available on the effect of such dietary measures on the survival characteristics of Salmonella in feces of pigs.…”
mentioning
confidence: 99%